Feasibility and Impact of Immunohistochemistry-based Molecular Subtyping for Muscle-invasive Bladder Cancer in Patients Treated with Radiation-based Therapy - Charles Hesswani; Chelsea L. Jackson; Gautier Marcq; Céline Hardy; Ronald Kool; Jose Joao Mansure; Fadi Brimo; David M. Berman; Wassim Kassouf (European Urology Open Science, 2023)
Background: Distinct molecular subtypes of muscle-invasive bladder cancer (MIBC) have been identified via gene expression profiling. Objective: We investigated the feasibility of a simple immunohistochemistry (IHC)-based Lund subtyping method and the association of MIBC subtypes with oncological outcomes for patients after bladder-preserving radiation-based therapy. Design, setting, and participants: Transurethral resected tumor tissues from 104 patients treated with radiation-based therapy were sampled on tissue microarray blocks. Outcome measurements and statistical analysis: The expression of KRT5, GATA3, and p16 proteins was scored via digital image analysis. Hierarchical clustering was used to classify tumors as the basal subtype or one of two luminal subtypes: genomically unstable (GU) or urothelial-like (URO). Subtypes were evaluated for association with complete response (CR), recurrence-free survival (RFS), and overall survival (OS). Results and limitations: The median OS was 43 mo (95% confidence interval 19–77) and median follow-up was 55 mo (interquartile range 39–75). Age and clinical stage had a significant impact on OS (p < 0.05). IHC-based subtype classification was feasible in most patients (89%). The subtype was basal in 23.6%, GU in 14.0%, URO in 31.2%, and unclassified in 31.2% of patients. No significant differences in CR, RFS, or OS were observed between the molecular subtypes. Limitations include the retrospective design and relatively small sample size. Conclusions: IHC-based molecular MIBC subtyping using a three-antibody algorithm is feasible in most patients treated with radiation-based therapy. MIBC subtype was not associated with response or survival. Further prospective studies are warranted to confirm the lack of association between molecular subtype and survival in patients treated with trimodal therapy. Patient summary: For patients with invasive bladder cancer treated with radiation-based therapy, we classified tumors into different subtypes using just three molecular stains. This method is cheaper and more widely available than the usual approach. However, we did not find an association between different cancer subtypes and survival.